Incidence, trend and distribution of transport-related injuries reported to health facilities in the Volta Region of Ghana, 2019 to 2023 - Victor Zeng; Williams Azumah Abanga; Samuel Adolf Bosoka; Maxwell Afetor; Christopher Sunkwa Tamal; Gyesi Razak Issahaku; Clement Tetteh Narh; Frank Baiden; Chrysantus Kubio (BMC Public Health)
Abstract Background Transport injuries are a global public health concern, causing 1.35 million deaths and over 20 million non-fatal injuries annually. Low- and middle-income countries, particularly countries in Africa, are experiencing an increase in fatalities. Ghana and the Volta Region are not exempted from the burden, prompting targeted interventions. In the development of these interventions, epidemiological data analysis is needed to identify areas for action. This study aimed to analyze the distribution, trends, and incidence of transport-related injuries in the Volta Region of Ghana. Method Secondary data was analyzed to describe transport-related injury cases and deaths in the Volta Region of Ghana from 2019 to 2023. Transport-related injuries were obtained from the monthly out-patient morbidity report form whereas transport related deaths were obtained from the inpatient morbidity and mortality, and cause of death report forms. Descriptive data analyses were performed and reported as frequencies, proportions, ratios, and choropleth maps. Result Of the 33,415 transport-related injury cases reported between 2019 and 2023, 25 were fatal. The highest proportion of cases, 35.8% (35.3–36.4), was among persons aged 20–34 years. About 66.0% (65.5–66.5) of all the cases involved males. The cumulative incidence was 387 injuries per 100,000 population with the highest incidence recorded in 2021. The incidence of cases declined from 357 per 100,000 population in 2019 to 320 per 100,000 population in 2023. The death rate was stable over the period with the highest of 1.2 per 1000 recorded in 2019 and declined from 1.2 per 1000 in 2019 to 0.9 per 1000 in 2023. Most, 56% of the deaths were reported in district hospitals. Conclusion The study showed a decreasing trend in the incidence of transport injuries, but a steady mortality rate in the Volta Region. Young adults were the highest affected group. There is the need for increased road safety campaigns and further research.